LO03: Application and usefulness of outpatient cardiac testing among emergency department patients with syncope. (15th May 2017) - Cook, O.; Mukarram, M.A.; Kim, S.; Arcot, K.; Taljaard, M.; Sivilotti, M.; Rowe, B.H.; Thiruganasambandamoorthy, V.
Abstract : Introduction: 2.6% of emergency department (ED) syncope patients will have underlying cardiac serious conditions (e.g. arrhythmia, serious structural heart disease) identified within 30-days of disposition. If those at risk are discharged home, outpatient cardiac testing can detect underlying arrhythmias and structural heart disease, and thereby improve patient safety. We describe the frequency of outpatient referrals for cardiac testing and the proportion of cardiac serious adverse events (SAE) among high risk and non-high (low and medium) risk ED syncope patients, as defined by the Canadian Syncope Risk Score (CSRS).Methods: We conducted a multicenter prospective cohort study to enroll adult syncope patients across five large tertiary care EDs. We collected demographics, medical history, disposition, CSRS value, outpatient referrals and testing results (holter, echocardiography), and cardiac SAE. Adjudicated 30-day SAE included death due to unknown cause, myocardial infarction, arrhythmia, and structural heart disease. We used descriptive analysis.Results: Of 4, 064 enrolled patients, a total of 955 patients (23%) received an outpatient referral (mean age 57.7 years, 52.1% female). Of the 299 patients (7%) hospitalized, 154 received outpatient cardiac testing after discharge. Among the 3, 765 patients discharged home from the ED, 40% of the non-high risk patients (305/756) and 56% of the high risk patients (25/45) received outpatient cardiac testing. Of all patients who received outpatient cardiac testing, 4 patients (0.8%) had serious cardiac conditions identified and all were arrhythmias. Among those with no cardiac testing, 5 patients (0.9%) suffered cardiac SAE (80% arrhythmias) outside the hospital. Of the 20 (44%) high risk patients who did not receive outpatient cardiac testing, 2 (10%) patients suffered arrhythmias outside the hospital. While among the 451 non-high risk patients, only 0.8% suffered arrhythmia outside the hospital.Conclusion: Outpatient cardiac testing among ED syncope patients is largely underutilized, especially among high risk patients. Better guidelines for outpatient cardiac testing are needed, as current practice is highly variable and mismatched with patient risk.